COMT and MAO-A Polymorphisms and Obsessive-Compulsive Disorder: A Family-Based Association Study - Sampaio, Aline Santos; Hounie, Ana Gabriela; Petribú, Kátia; Cappi, Carolina; Morais, Ivanil; Vallada, Homero; do Rosário, Maria Conceição; Stewart, S. Evelyn; Fargeness, Jesen; Mathews, Carol; Arnold, Paul; Hanna, Gregory L.; et al. (PLOS ONE, 2015)
Objective Obsessive-compulsive disorder (OCD) is a common and debilitating psychiatric illness. Although a genetic component contributes to its etiology, no single gene or mechanism has been identified to the OCD susceptibility. The catechol-O-methyltransferase (COMT) and monoamine oxidase A (MAO-A) genes have been investigated in previous OCD studies, but the results are still unclear. More recently, Taylor (2013) in a comprehensive meta-analysis of genetic association studies has identified COMT and MAO-A polymorphisms involved with OCD. In an effort to clarify the role of these two genes in OCD vulnerability, a family-based association investigation was performed as an alternative strategy to the classical case-control design. Methods Transmission disequilibrium analyses were performed after genotyping 13 single-nucleotide polymorphisms (eight in COMT and five in MAO-A) in 783 OCD trios (probands and their parents). Four different OCD phenotypes (from narrow to broad OCD definitions) and a SNP x SNP epistasis were also analyzed. Results OCD, broad and narrow phenotypes,were not associated with any of the investigated COMT and MAO-A polymorphisms. In addition, the analyses of gene-gene interaction did not show significant epistatic influences on phenotype between COMT and MAO-A. Conclusions The findings do not support an association between DSM-IV OCD and the variants of COMT or MAO-A. However, results from this study cannot exclude the contribution of these genes in the manifestation of OCD. The evaluation of broader spectrum phenotypes could help to understand the role of these and other genes in the pathophysiology of OCD and its spectrum disorders.